2019
DOI: 10.1155/2019/6021037
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Risk Factors of Lung Cancer-Associated Acute Ischemic Stroke

Abstract: Objective. To research the clinical characteristics and risk factors of lung cancer-associated acute ischemic stroke (LCA-AIS). Methods. Patients diagnosed with LCA-AIS, simple lung cancer, and simple AIS were enrolled. The primary information, laboratory results, tumor histopathology, neurological deficits, and survival time of the patients were collected and analyzed. Results. (1) In the LCA-AIS group, the pathology of 69.56% patients were adenocarcinoma, and the proportion of poorly differentiated patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The patient's laboratory results suggested D-dimer, thrombin time, CA125, CA19-9, and CYFRA21-1 were significantly abnormal, which were similar to the risk factors of lung cancer-associated AIS. 10,11 In terms of imaging findings, the AIS lesions involved bilateral cerebral hemispheres and anterior and posterior circulation, which meet the characteristics of cancer-associated AIS. 12 A randomized controlled study found that the initial symptoms of neurological deficits in patients with wake-up stroke were usually mild.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The patient's laboratory results suggested D-dimer, thrombin time, CA125, CA19-9, and CYFRA21-1 were significantly abnormal, which were similar to the risk factors of lung cancer-associated AIS. 10,11 In terms of imaging findings, the AIS lesions involved bilateral cerebral hemispheres and anterior and posterior circulation, which meet the characteristics of cancer-associated AIS. 12 A randomized controlled study found that the initial symptoms of neurological deficits in patients with wake-up stroke were usually mild.…”
Section: Discussionmentioning
confidence: 78%
“…Our previous research suggested that the median survival time of patients with lung cancer-associated AIS was only 5 months. 10 However, we followed up with the patient for 10 months and AIS did not occur again.…”
Section: Discussionmentioning
confidence: 98%
“…It was also found that lung cancer had worse prognosis with highest rates of in-hospital mortality, cerebral edema, pneumonia, non-routine discharge and intracranial hemorrhage. One explanation for increased complications is that the interaction between lung cancer and AIS may shorten patients' life expectancy and worsen their quality of life [38]. Another retrospective study based on the SEER database also found that stroke mortality was significantly increased in patients with lung cancer compared with the general population (standardized mortality ratios 1.73, 95% CI 1.69-1.78) [39].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with LUAD combined with AIS, LUAD occurs due to the occurrence of AIS. The prevalence of lung cancer in the stroke cohort was 5.3 per 1000 person-years ( 27 , 28 ). Lung cancer patients are most likely to experience a stroke within one year after diagnosis.…”
Section: Discussionmentioning
confidence: 99%